Anti-democratic political parties as a threat to democracy: Models of reaction and the strategic democracy - Kouroutakis, Antonios (Thomson Reuters, 2018)
There is a consensus among policymakers, lawmakers, legal scholars and ‘we the people’ in the western world, that democracy is a blessing. However, how do we defend democracy from anti-democratic political parties that aim to overthrow the democratic regime by abusing the guarantees and the tolerance of democracy? This article argues that there are three public policy options: the traditional model that permits the dissolution of anti-democratic political parties; the business as usual model, that regulates such parties with ordinary administrative law and controls the conduct of their members via ordinary criminal law; and finally, the strategic model that employs an electoral system according to which political parties, like the anti-democratic, having more enemies than supporters are ostracized. That said, this article argues that whilst electoral law is the most rule-of-law based mechanism to safeguard democracies from anti-democratic parties, not all electoral systems are capable. Only the electoral systems that allow for ‘strategic voting’ can be employed for this purpose.
Keywords: Antidemocratic political parties; Strategic democracy; Electoral law; 59 Ciencia Política::5905 Vida política::5905.02 Comportamiento político; ODS 16 - Paz, justicia e instituciones sólidas